Individualized Ablation of Hepatocellular Carcinoma: Tailored Approaches across the Phenotype Spectrum - Devcic, Zlatko; Elboraey, Mohamed; Vidal, Lucas; Mody, Kabir; Harnois, Denise; Patel, Tushar; Toskich, Beau B. (Seminars in Interventional Radiology, 2019)
Ablation is now recommended by international guidelines for the definitive treatment of hepatocellular carcinoma (HCC). Extensive clinical studies have demonstrated outcomes comparable to surgical resection with shorter hospital stays, decreased costs, and improved quality of life. Successful ablation requires complete treatment of both tumor and margin while preserving critical adjacent structures. HCC exhibits highly variable presentations in both anatomic involvement and biology which have significant implications on choice of ablative therapy. There are now abundant ablation modalities and adjunctive techniques which can be used to individualize ablation and maximize curative results. This article provides a patient-centered summary of approaches to HCC ablation in the context of patient performance, hepatic reserve, tumor phenotype and biology, intra- and extrahepatic anatomy, and ablation technology.
Keywords: hepatocellular carcinoma; locoregional therapy; ablation